Ancient warfare - Sidebottom, Harry (Oxford ; New York : Oxford University Press, 2004)
"This book explores the ways in which ancient society thought about conflict. Many aspects of ancient warfare are examined from philosophy to the technical skills needed to fight"--Provided by publisher.
Includes bibliographical references (p. 129-150) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Military art and science -- History -- To 500.; Military history, Ancient; Civilization, Western; Electronic books